The use of English Conversation Journal (ECJ) to improve students’ speaking performance in business English communication - Mera Intan; Kismullah Abdul Muthalib; Iskandar Abdul Samad (English Education Journal, 2021)
This experimental research was intended to make an analysis and assessment toward the use of English Conversation Journal (ECJ) whether it is effective to improve students’ speaking performance in Business English Communication or not. The objectives of this study were to find out whether there are any significant differences between students who are taught by using ECJ and without ECJ in terms of students’ speaking performance in Business English Communication. The Researcher employed quantitative research with two groups consisting of pre-test and post-test groups through random sampling where Office Management students (OM-35) as control class and (OM-36) as experimental class. The result revealed that the mean difference is 11.75. It showed that the average result of students’ deviation score in Control and Experiment groups was 69.50-81.25=-11.75. In other words, there are significant differences in students’ Speaking Performance in Business English Communication between those who were taught by using English Conversation Journal (ECJ) and those who were not. Therefore, improving student’s speaking performance in Business English Communication by using English Conversation Journal (ECJ) can be an alternative in teaching and learning process.